동해 남한국대지 퇴적물의 생물기원 성분 입도 분포의 특성과 고해양학적 의미 - 장준호; 박장준; 김은정; 엄인권; Jang, Jun-Ho; Bahk, Jang-Jun; Kim, Eun-Jung; Um, In-Kwon (Ocean and polar research, 2020)
This study details grain-size distributions (GSDs) of carbonate and biogenic opal fractions of the sediments retrieved from the South Korea Plateau in the East Sea and draws paleocanographic implications from them. The opal-fraction GSDs show fine modes of 10.3 ㎛ and coarse modes of 102.5 ㎛ on average. The fine-mode grains of opal fractions mainly consist of small diatoms and radiolarians including their broken frustules, while the coarse-mode grains are mostly comprised of large warm-water diatoms and radiolarians. Significant positive correlation between opal contents and abundances of the coarse-mode GSDs in the total GSDs suggests that the abundances of the coarse-mode GSDs were controlled by the increased surface productivity of warm-water diatoms during interglacial stages. The carbonate-fraction GSDs show fine modes of 2.4 ㎛ and coarse modes of 99.1 ㎛ on average. The fine-mode grains mainly consist of coccolithophores, while the coarse-mode grains are mostly comprised of intact or broken planktonic foraminifera. The abundances of coarse-mode and fine-mode GSDs were not correlated with carbonate contents, suggesting a complex control exerted by both the degree of carbonate dissolution and the productivity of coccolithophores on the carbonate-fraction GSDs.